Pseudomyxoma peritonei: two case study and literatures review - Alsubaiee, Ibrahim F. (International Surgery Journal, 2020)
Pseudomyxoma peritonei (PMP) is a rare neoplastic illness with unique clinical and pathologic patterns. This disease characterized by being chronic, indolent, and relapsing. It is diagnostically challenging and very vague disease. It characterized by huge amounts of thick mucinous ascites with multiple omental and peritoneal implants that is gradually fill the abdominal and pelvic cavities. The most common clinical features are progressive abdominal distention with increase in the abdominal girth. Diagnosis of Pseudomyxoma peritonei (PMP) is usually difficult due to its vague symptoms especially in the early stages. Ultrasound examination is very useful and generally has pictures similar to that of CT scan images. Treatment of Pseudomyxoma peritonei (PMP) is cytoreductive (debulking) surgery to remove the mucin and the tumor implants in the peritoneal cavity. This is followed by intraoperative hyperthermic peritoneal chemotherapy (HIPEC). Recurrence of pseudomyxoma peritonei (PMP) patients is quite common as particularly when the disease is diagnosed and treated in the late stage.